2023
DOI: 10.1007/s44246-023-00053-5
|View full text |Cite
|
Sign up to set email alerts
|

Does micro/nano biochar always good to phytoremediation? A case study from multiple metals contaminated acidic soil using Salix jiangsuensis '172'

Jiang Xiao,
Xiaogang Li,
Yini Cao
et al.

Abstract: Biochar amendments have shown great superiority in reduction of heavy metals (HM) toxicity and soil amelioration in severely contaminated mining areas, which suggested to facilitate vegetation rehabilitation using fast-growing trees. Bone biochar (BC) and ball-milled bone biochar (MBC) were fabricated by pyrolyzing bone meal at 600°C followed by eco-friendly wet-milling techniques. The effect of BC and MBC application (0, 0.5, 1.0, 2.0 and 4.0 wt%) on soil properties, plant growth and metal accumulation of Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 93 publications
2
6
0
Order By: Relevance
“…However, the quantities of Cu and Pb in roots were higher than in stems and leaves across all treatments (Article III), indicating that high concentrations of Cu and Pb were retained in the roots of the plants. These results are consistent with those of Xiao et al (2023), who reported that, in a pot experiment, Cd was mainly found in the leaves of Salix cultivated in CAPF soil, but Cu and Pb were primarily found in the roots. Additionally, in similar CAPF soil, Quercus texana leaves and Q. pagoda leaves contained higher levels of Cd than their roots.…”
Section: Growth and Metal Accumulation Of Salix Seedlings With Differ...supporting
confidence: 93%
See 4 more Smart Citations
“…However, the quantities of Cu and Pb in roots were higher than in stems and leaves across all treatments (Article III), indicating that high concentrations of Cu and Pb were retained in the roots of the plants. These results are consistent with those of Xiao et al (2023), who reported that, in a pot experiment, Cd was mainly found in the leaves of Salix cultivated in CAPF soil, but Cu and Pb were primarily found in the roots. Additionally, in similar CAPF soil, Quercus texana leaves and Q. pagoda leaves contained higher levels of Cd than their roots.…”
Section: Growth and Metal Accumulation Of Salix Seedlings With Differ...supporting
confidence: 93%
“…Similarly, Padoan et al (2020) concluded that Salix clones accumulated the highest amount of Cu in stems. Metal accumulation varied within the different tissues of the plant and between treatments (Li et al 2022b;Xiao et al 2023). The results of this study (Article III) are also consistent with those reported by Rattan et al (2005) and Irshad et al (2015).…”
Section: Growth and Metal Accumulation Of Salix Seedlings With Differ...supporting
confidence: 91%
See 3 more Smart Citations